Fast Artificial Bee Colony for Clustering - Girsang, Abba Suganda; Mulyono, Yohan; Fanny, Fanny (Informatica, 2017)
Artificial Bee Colony (ABC) is one of good heuristic intelligent algorithm to solve optimization problem including clustering. Generally, the heuristic algorithm will take the high computation time to solve optimization problem. Likewise, ABC also consumes the much time to solve clustering problem. This paper intends solving clustering problem using ABC with focusing reduction computation time called FABCC. This idea proposes detecting the pattern of redundant process then compacting it to effective process to diminish the computation process. There are five data sets to be used to prove the performance of FABCC. The results shows that FABCC is effective to prune the duration process up to 46.58 %.